2012
DOI: 10.1128/cvi.05388-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plaque- and Enzyme-Linked Immunospot-Based Assays To Measure the Neutralizing Activities of Monoclonal Antibodies Specific to Domain III of Dengue Virus Envelope Protein

Abstract: The plaque reduction neutralization test (PRNT) is used widely to measure the neutralization activity of anti-dengue virus (DENV) antibodies, but it is time-consuming and labor-intensive and has low sample throughput. For fast and convenient measurement of neutralizing antibodies, especially in evaluating the efficiency of the DENV vaccines on a large scale, a new method is needed to replace PRNT. In recent decades, several microneutralization assays have been developed to overcome the limitations of PRNT. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…8,21,23,26 A recent study showed that ELISPOT-MNT had a sensitivity of 95.6% and specificity of 88.2%, with a good correlation (R 2 = 0.7) with PRNT. 16 Because of its very high sensitivity, the use of ELISPOT-MNT as the comparative standard method in our study leads inevitably to lower statistics performances of the assays that are compared with it, which can explain the relatively low performances of both diagnostic strategies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…8,21,23,26 A recent study showed that ELISPOT-MNT had a sensitivity of 95.6% and specificity of 88.2%, with a good correlation (R 2 = 0.7) with PRNT. 16 Because of its very high sensitivity, the use of ELISPOT-MNT as the comparative standard method in our study leads inevitably to lower statistics performances of the assays that are compared with it, which can explain the relatively low performances of both diagnostic strategies.…”
Section: Discussionmentioning
confidence: 92%
“…14 However, standard methods such as HI and PRNT are labor intensive, time consuming and require acute and convalescent sera with an interval of more than 7 days, which makes them inadequate for routine early diagnosis. 15 Thus, 16 In 2010, Colombia experienced the worst dengue outbreak in its history. During this epidemic year and the following post-epidemic period, an active surveillance study of dengue cases in schoolchildren was performed in the Colombian City of Medellin.…”
mentioning
confidence: 99%
“…These new tests have been separately validated, compared and evaluated [124,[126][127][128][129][130] against PRNT and found to have good agreement (false-positive rate <10%) in cases with primary DENV infection [124,130]. However, Putnak et al reported poor agreement among the tests in association with vaccination or secondary infection [124].…”
Section: Dengue Neutralizing Antibody Detectionmentioning
confidence: 99%
“…Enzyme-linked immunospot and microneutralization tests (ELISPOT-MNT) [21] were performed in 278 serum samples following a standardized previously published protocol [22]. The ELISPOT-MNT 50 titer was determined as the serum dilution that reduces the number of foci or plaques by at least 50% when compared with wells with virus control.…”
Section: Methodsmentioning
confidence: 99%